IDENTIFICATION, ASSESSMENT AND MAPPING OF GEOTHERMAL RESOURCE IN MANONG, PERAK WITH EMPHASIS ON ELECTRICAL RESISTIVITY - KEARABILWE, INNOCENT MASOBE (Universiti Teknologi PETRONAS, 2014)
This report entails the geological study of Manong, Perak with emphasis on its geothermal resource (thermal spring). The project was divided into two parts; the first part consisted of data collection in a form of review of publications and traversing. The second part focused on the geophysical study of the area with regards to Electrical Resistivity Survey. River and road traversing were key milestones in mapping during which outcrops were identified in approximately 1 sq.km range of the study area. The outcrops encountered were granite and sandstone. A lithological map constructed shows that granite and sandstone are dominant Lithologies; sandstone lies between two granite beds. The thermal spring is located on the sandstone bed. All outcrops had a common type of deformation which was joints. The polarplots of this formation revealed two possible fracture systems in the area. The dominant fracture system trends Northeast-Southwest (NE-SW) whilst the minor fracture system trends Northwest-Southeast (NW-SE). Two lines of Electrical Resistivity were surveyed 200m apart. The inversion models revealed that the fracture system in the thermal spring trends NW-SE parallel to the Bentong-Raub Suture Zone. Petrographic analysis of the granite samples suggests the resistivity of the granite may be affected by micro fractures.